Improving Student’s Creative Thinking Skills through Project Based Learning on the Material of Nets of Cubes and Beams of Class IV SDN 03 Waru - Sigit Purnomo (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Creative thinking skills have four indicators that need to be mastered by students including fluency, flexibility, originality, and elaboration. This research uses the Classroom Action Research method. The subjects of this study were fourth grade students with a total of 13 students consisting of 7 boys and 6 girls. Data collection techniques using observation, tests, and documentation. Data analysis techniques were descriptive and presented in form of bar charts. The results of this study indicate that average creative thinking skills of students in cycle 1 have increased, namely 62.30% Results of implementation of cycle 2 obtained average creative thinking skills of students to 76.15%. Overall, the use of learning models on the cube net material has increased by 35.39%. Through the application of the project-based learning model helps improve creative thinking skills in the material of the nets of cubes and beams of class IV at SDN 03 Waru.